1992
DOI: 10.1111/j.1399-6576.1992.tb03538.x
|View full text |Cite
|
Sign up to set email alerts
|

Ten ml bupivacaine 0.125% with 12.5 μg epinephrine is a reliable epidural test dose to detect inadvertent intravascular injection in obstetric patients. A double‐blind study

Abstract: A double-blind study was designed in order to determine the specificity and sensitivity of an epidural test dose to detect inadvertent intravenous injection in obstetric patients undergoing epidural analgesia. Forty unselected obstetric patients were given an intravenous injection of 10 ml bupivacaine 0.125% with 12.5 micrograms epinephrine (test dose) or 10 ml normal physiologic saline. The maternal heart rate was monitored by the direct ECG mode of a fetal monitor and registered simultaneously with the tocog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…On the other hand, Gieraerts et aL 21 showed that in labouring women sensitivity and specificity remained unchanged after lowthoracic epidural analgesia was established. These observations imply that our present results could be influenced by the extent of epidural neural blockade, especially if the block level reached high thoracic dermatomes.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Gieraerts et aL 21 showed that in labouring women sensitivity and specificity remained unchanged after lowthoracic epidural analgesia was established. These observations imply that our present results could be influenced by the extent of epidural neural blockade, especially if the block level reached high thoracic dermatomes.…”
Section: Discussionmentioning
confidence: 98%
“…Detecting intravenous placement relies on evidence from an awake patient of unusual symptoms such as peri‐oral tingling and tinnitus. The addition of adrenaline to test doses may help to indicate intravenous placement in young, fit adults [4]. However, studies in elderly patients taking antihypertensive or anti‐anginal medication have demonstrated very varying responses to similar doses of adrenaline [5] particularly if receiving a nitrous oxide and isoflurane anaesthetic [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research resulted in the recommendation that "Every dose given in obstetric epidural analgesia can be a test dose", consisting of 10 ml of bupivacaine 0.125% + epinephrine 1;800,000, which is 12.5 mg of bupivacaine and 12.5 µg of epinephrine. This dose allows detection of intravascular injection as it produces an identifiable tachycardia for 30 s, with a slowing of the uterine contractions in such a way that one or two contractions are skipped or reduced in intensity (24)(25)(26). Aspiration is recommended before any injection via the epidural catheter but may not be entirely reliable in showing blood.…”
Section: Safety Issues In Anesthesia For Obstetric Patientsmentioning
confidence: 99%